Effectiveness of supervised physiotherapy versus a home exercise program in patients with distal radius fracture: a randomized controlled trial with a 2-year follow-up - Gutiérrez Espinoza, Héctor J.; Gutiérrez Monclus, Rodrigo.; Román Veas, Javier.; Valenzuela Fuenzalida, Juan José.; Hagertf, Elisabet; Araya Quintanilla, Felipe. (Elsevier, 2024)
Objective: To determine in the long term whether supervised physiotherapy is more effective than a home exercise program for functional improvement and pain relief in patients with distal radius fracture (DRF). Design: Randomized controlled trial. Setting: Rehabilitation hospital. Participants: A total of 74 patients older than 60 years with extra-articular DRF were randomly allocated into two groups. Interventions: The experimental group received 6 weeks of supervised physiotherapy (n = 37) and the control group received 6 weeks of home exercise program (n = 37). Main outcome measures: The primary outcome was wrist/hand function assessed using the Patient-Rated Wrist Evaluation (PRWE) questionnaire; secondary outcomes were the pain visual analogue scale (VAS), grip strength and wrist flexion–extension active range of motion. Results: All patients completed the trial. For the primary outcome, at 6-weeks and 1-year follow-up, the PRWE questionnaire showed a mean difference between groups of 18.6 (95% CI 12.8 to 24.3) and 18.5 points (95% CI 12.7 to 24.2) respectively, these differences are clinically important. Conversely, at 2-year follow-up this effect decreases to 3.3 points (95% CI −2.4 to 9.0). For secondary outcomes, at 6-weeks and 1-year follow-up, in all measurements the effect size range from medium to large. Conversely, at 2-year follow-up only grip strength showed large effect size in favor of supervised physiotherapy, the rest of outcomes did not show difference between groups. Conclusion: At the 6-week and 1-year follow-up, supervised physiotherapy was more effective for functional improvement and pain relief compared with a home exercise program in patients older than 60 years with extra-articular DRF. However, this effect decreases over time, at the 2-year follow-up, only grip strength showed a difference in favor of supervised physiotherapy. Trial registration: Brazilian registry of clinical trials UTN no. U1111- 1249-2492. Registered 17 March 2020. Contribution of the Paper: • Current evidence has shown controversial results regarding the effectiveness of supervised physiotherapy versus a home exercise program in elderly patients with DRFs. • At the 6-week and 1-year follow-up, supervised physiotherapy is more effective for functional improvement and pain relief. • However, at the 2-year follow-up, only grip strength showed a difference in favor of supervised physiotherapy in these patients.
Keywords: Supervised physiotherapy; Ancianos; Ensayos controlados aleatorios; Fracturas del radio distal